Datasets:

Modalities:
Text
Languages:
English
Libraries:
Datasets
License:
File size: 30,527 Bytes
4365a98
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
fc5e983
4365a98
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
 
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
325
326
327
328
329
330
331
332
333
334
335
336
337
338
339
340
341
342
343
344
345
346
347
348
349
350
351
352
353
354
355
356
357
358
359
360
361
362
363
364
365
366
367
368
369
370
371
372
373
374
375
376
377
378
379
380
381
382
383
384
385
386
387
388
389
390
391
392
393
394
395
396
397
398
399
400
401
402
403
404
405
406
407
408
409
410
411
412
413
414
415
416
417
418
419
420
421
422
423
424
425
426
427
428
429
430
431
432
433
434
435
436
437
438
439
440
441
442
443
444
445
446
447
448
449
450
451
452
453
454
455
456
457
458
459
460
461
462
463
464
465
466
467
468
469
470
471
472
473
474
475
476
477
478
479
480
481
482
483
484
485
486
487
488
489
490
491
492
493
494
495
496
497
498
499
500
501
502
503
504
505
506
507
508
509
510
511
512
513
514
515
516
517
518
519
520
521
522
523
524
525
526
527
528
529
530
531
532
533
534
535
536
537
538
539
540
541
542
543
544
545
546
547
548
549
550
551
552
553
554
555
556
557
558
559
560
561
562
563
564
565
566
567
568
569
570
571
572
573
574
575
576
577
578
579
580
581
582
583
584
585
586
587
588
589
590
591
592
593
594
595
596
597
598
599
600
601
602
603
604
605
606
607
608
609
610
611
612
613
614
615
616
617
618
619
620
621
622
623
624
625
626
627
628
629
630
631
632
633
634
635
636
637
638
639
640
641
642
643
644
645
646
647
648
649
650
651
652
653
654
655
656
657
658
659
660
661
662
663
664
665
666
667
668
669
670
671
672
673
674
675
676
677
678
679
680
681
682
683
684
685
686
687
688
689
690
691
692
693
694
695
696
697
698
699
700
701
702
703
704
705
706
707
708
709
710
711
712
713
714
715
716
717
718
719
720
721
722
723
724
725
726
727
728
729
730
731
732
733
734
735
736
737
738
739
740
741
742
743
744
745
746
747
748
749
750
751
752
753
754
755
756
757
758
759
760
761
762
763
764
765
766
767
768
769
770
771
772
773
774
775
776
777
778
779
780
781
782
783
784
785
786
787
788
789
790
791
792
793
794
795
796
797
798
799
/-
Copyright (c) 2021 Scott Morrison. All rights reserved.
Released under Apache 2.0 license as described in the file LICENSE.
Authors: Scott Morrison
-/
import algebra.homology.additive
import tactic.abel

/-!
# Chain homotopies

We define chain homotopies, and prove that homotopic chain maps induce the same map on homology.
-/

universes v u

open_locale classical
noncomputable theory

open category_theory category_theory.limits homological_complex

variables {ι : Type*}
variables {V : Type u} [category.{v} V] [preadditive V]

variables {c : complex_shape ι} {C D E : homological_complex V c}
variables (f g : C ⟶ D) (h k : D ⟶ E) (i : ι)

section

/-- The composition of `C.d i i' ≫ f i' i` if there is some `i'` coming after `i`,
and `0` otherwise. -/
def d_next (i : ι) : (Π i j, C.X i ⟶ D.X j) →+ (C.X i ⟶ D.X i) :=
add_monoid_hom.mk' (λ f, C.d i (c.next i) ≫ f (c.next i) i) $
λ f g, preadditive.comp_add _ _ _ _ _ _

/-- `f i' i` if `i'` comes after `i`, and 0 if there's no such `i'`.
Hopefully there won't be much need for this, except in `d_next_eq_d_from_from_next`
to see that `d_next` factors through `C.d_from i`. -/
def from_next (i : ι) : (Π i j, C.X i ⟶ D.X j) →+ (C.X_next i ⟶ D.X i) :=
add_monoid_hom.mk' (λ f, f (c.next i) i) $ λ f g, rfl

@[simp]
lemma d_next_eq_d_from_from_next (f : Π i j, C.X i ⟶ D.X j) (i : ι) :
  d_next i f = C.d_from i ≫ from_next i f := rfl

lemma d_next_eq (f : Π i j, C.X i ⟶ D.X j) {i i' : ι} (w : c.rel i i') :
  d_next i f = C.d i i' ≫ f i' i :=
by { obtain rfl := c.next_eq' w, refl }

@[simp] lemma d_next_comp_left (f : C ⟶ D) (g : Π i j, D.X i ⟶ E.X j) (i : ι) :
  d_next i (λ i j, f.f i ≫ g i j) = f.f i ≫ d_next i g :=
(f.comm_assoc _ _ _).symm

@[simp] lemma d_next_comp_right (f : Π i j, C.X i ⟶ D.X j) (g : D ⟶ E) (i : ι) :
  d_next i (λ i j, f i j ≫ g.f j) = d_next i f ≫ g.f i :=
(category.assoc _ _ _).symm

/-- The composition of `f j j' ≫ D.d j' j` if there is some `j'` coming before `j`,
and `0` otherwise. -/
def prev_d (j : ι) : (Π i j, C.X i ⟶ D.X j) →+ (C.X j ⟶ D.X j) :=
add_monoid_hom.mk' (λ f, f j (c.prev j) ≫ D.d (c.prev j) j) $
λ f g, preadditive.add_comp _ _ _ _ _ _

/-- `f j j'` if `j'` comes after `j`, and 0 if there's no such `j'`.
Hopefully there won't be much need for this, except in `d_next_eq_d_from_from_next`
to see that `d_next` factors through `C.d_from i`. -/
def to_prev (j : ι) : (Π i j, C.X i ⟶ D.X j) →+ (C.X j ⟶ D.X_prev j) :=
add_monoid_hom.mk' (λ f, f j (c.prev j)) $ λ f g, rfl

@[simp]
lemma prev_d_eq_to_prev_d_to (f : Π i j, C.X i ⟶ D.X j) (j : ι) :
  prev_d j f = to_prev j f ≫ D.d_to j := rfl

lemma prev_d_eq (f : Π i j, C.X i ⟶ D.X j) {j j' : ι} (w : c.rel j' j) :
  prev_d j f = f j j' ≫ D.d j' j :=
by { obtain rfl := c.prev_eq' w, refl }

@[simp] lemma prev_d_comp_left (f : C ⟶ D) (g : Π i j, D.X i ⟶ E.X j) (j : ι) :
  prev_d j (λ i j, f.f i ≫ g i j) = f.f j ≫ prev_d j g :=
category.assoc _ _ _

@[simp] lemma prev_d_comp_right (f : Π i j, C.X i ⟶ D.X j) (g : D ⟶ E) (j : ι) :
  prev_d j (λ i j, f i j ≫ g.f j) = prev_d j f ≫ g.f j :=
by { dsimp [prev_d], simp only [category.assoc, g.comm] }

lemma d_next_nat (C D : chain_complex V ℕ) (i : ℕ) (f : Π i j, C.X i ⟶ D.X j) :
  d_next i f = C.d i (i-1) ≫ f (i-1) i :=
begin
  dsimp [d_next],
  cases i,
  { simp only [shape, chain_complex.next_nat_zero, complex_shape.down_rel,
      nat.one_ne_zero, not_false_iff, zero_comp], },
  { dsimp only [nat.succ_eq_add_one],
    have : (complex_shape.down ℕ).next (i + 1) = i + 1 - 1,
    { rw chain_complex.next_nat_succ, refl },
    congr' 2, }
end

lemma prev_d_nat (C D : cochain_complex V ℕ) (i : ℕ) (f : Π i j, C.X i ⟶ D.X j) :
  prev_d i f = f i (i-1) ≫ D.d (i-1) i :=
begin
  dsimp [prev_d],
  cases i,
  { simp only [shape, cochain_complex.prev_nat_zero, complex_shape.up_rel,
      nat.one_ne_zero, not_false_iff, comp_zero]},
  { dsimp only [nat.succ_eq_add_one],
    have : (complex_shape.up ℕ).prev (i + 1) = i + 1 - 1,
    { rw cochain_complex.prev_nat_succ, refl },
    congr' 2, },
end

/--
A homotopy `h` between chain maps `f` and `g` consists of components `h i j : C.X i ⟶ D.X j`
which are zero unless `c.rel j i`, satisfying the homotopy condition.
-/
@[ext, nolint has_nonempty_instance]
structure homotopy (f g : C ⟶ D) :=
(hom : Π i j, C.X i ⟶ D.X j)
(zero' : ∀ i j, ¬ c.rel j i → hom i j = 0 . obviously)
(comm : ∀ i, f.f i = d_next i hom + prev_d i hom + g.f i . obviously')

variables {f g}
namespace homotopy

restate_axiom homotopy.zero'

/--
`f` is homotopic to `g` iff `f - g` is homotopic to `0`.
-/
def equiv_sub_zero : homotopy f g ≃ homotopy (f - g) 0 :=
{ to_fun := λ h,
  { hom := λ i j, h.hom i j,
    zero' := λ i j w, h.zero _ _ w,
    comm := λ i, by simp [h.comm] },
  inv_fun := λ h,
  { hom := λ i j, h.hom i j,
    zero' := λ i j w, h.zero _ _ w,
    comm := λ i, by simpa [sub_eq_iff_eq_add] using h.comm i },
  left_inv := by tidy,
  right_inv := by tidy, }

/-- Equal chain maps are homotopic. -/
@[simps]
def of_eq (h : f = g) : homotopy f g :=
{ hom := 0,
  zero' := λ _ _ _, rfl,
  comm := λ _, by simp only [add_monoid_hom.map_zero, zero_add, h] }

/-- Every chain map is homotopic to itself. -/
@[simps, refl]
def refl (f : C ⟶ D) : homotopy f f :=
of_eq (rfl : f = f)

/-- `f` is homotopic to `g` iff `g` is homotopic to `f`. -/
@[simps, symm]
def symm {f g : C ⟶ D} (h : homotopy f g) : homotopy g f :=
{ hom := -h.hom,
  zero' := λ i j w, by rw [pi.neg_apply, pi.neg_apply, h.zero i j w, neg_zero],
  comm := λ i, by rw [add_monoid_hom.map_neg, add_monoid_hom.map_neg, h.comm, ← neg_add,
      ← add_assoc, neg_add_self, zero_add] }

/-- homotopy is a transitive relation. -/
@[simps, trans]
def trans {e f g : C ⟶ D} (h : homotopy e f) (k : homotopy f g) : homotopy e g :=
{ hom := h.hom + k.hom,
  zero' := λ i j w, by rw [pi.add_apply, pi.add_apply, h.zero i j w, k.zero i j w, zero_add],
  comm := λ i, by { rw [add_monoid_hom.map_add, add_monoid_hom.map_add, h.comm, k.comm], abel }, }

/-- the sum of two homotopies is a homotopy between the sum of the respective morphisms. -/
@[simps]
def add {f₁ g₁ f₂ g₂ : C ⟶ D}
  (h₁ : homotopy f₁ g₁) (h₂ : homotopy f₂ g₂) : homotopy (f₁+f₂) (g₁+g₂) :=
{ hom := h₁.hom + h₂.hom,
  zero' := λ i j hij, by
    rw [pi.add_apply, pi.add_apply, h₁.zero' i j hij, h₂.zero' i j hij, add_zero],
  comm := λ i, by
    { simp only [homological_complex.add_f_apply, h₁.comm, h₂.comm,
        add_monoid_hom.map_add],
      abel, }, }

/-- homotopy is closed under composition (on the right) -/
@[simps]
def comp_right {e f : C ⟶ D} (h : homotopy e f) (g : D ⟶ E) : homotopy (e ≫ g) (f ≫ g) :=
{ hom := λ i j, h.hom i j ≫ g.f j,
  zero' := λ i j w, by rw [h.zero i j w, zero_comp],
  comm := λ i, by simp only [h.comm i, d_next_comp_right, preadditive.add_comp,
    prev_d_comp_right, comp_f], }

/-- homotopy is closed under composition (on the left) -/
@[simps]
def comp_left {f g : D ⟶ E} (h : homotopy f g) (e : C ⟶ D) : homotopy (e ≫ f) (e ≫ g) :=
{ hom := λ i j, e.f i ≫ h.hom i j,
  zero' := λ i j w, by rw [h.zero i j w, comp_zero],
  comm := λ i, by simp only [h.comm i, d_next_comp_left, preadditive.comp_add,
    prev_d_comp_left, comp_f], }

/-- homotopy is closed under composition -/
@[simps]
def comp {C₁ C₂ C₃ : homological_complex V c} {f₁ g₁ : C₁ ⟶ C₂} {f₂ g₂ : C₂ ⟶ C₃}
  (h₁ : homotopy f₁ g₁) (h₂ : homotopy f₂ g₂) : homotopy (f₁ ≫ f₂) (g₁ ≫ g₂) :=
(h₁.comp_right _).trans (h₂.comp_left _)

/-- a variant of `homotopy.comp_right` useful for dealing with homotopy equivalences. -/
@[simps]
def comp_right_id {f : C ⟶ C} (h : homotopy f (𝟙 C)) (g : C ⟶ D) : homotopy (f ≫ g) g :=
(h.comp_right g).trans (of_eq $ category.id_comp _)

/-- a variant of `homotopy.comp_left` useful for dealing with homotopy equivalences. -/
@[simps]
def comp_left_id {f : D ⟶ D} (h : homotopy f (𝟙 D)) (g : C ⟶ D) : homotopy (g ≫ f) g :=
(h.comp_left g).trans (of_eq $ category.comp_id _)

/-!
Null homotopic maps can be constructed using the formula `hd+dh`. We show that
these morphisms are homotopic to `0` and provide some convenient simplification
lemmas that give a degreewise description of `hd+dh`, depending on whether we have
two differentials going to and from a certain degree, only one, or none.
-/

/-- The null homotopic map associated to a family `hom` of morphisms `C_i ⟶ D_j`.
This is the same datum as for the field `hom` in the structure `homotopy`. For
this definition, we do not need the field `zero` of that structure
as this definition uses only the maps `C_i ⟶ C_j` when `c.rel j i`. -/
def null_homotopic_map (hom : Π i j, C.X i ⟶ D.X j) : C ⟶ D :=
{ f      := λ i, d_next i hom + prev_d i hom,
  comm'  := λ i j hij,
  begin
    have eq1 : prev_d i hom ≫ D.d i j = 0,
    { simp only [prev_d, add_monoid_hom.mk'_apply, category.assoc, d_comp_d, comp_zero], },
    have eq2 : C.d i j ≫ d_next j hom = 0,
    { simp only [d_next, add_monoid_hom.mk'_apply, d_comp_d_assoc, zero_comp], },
    rw [d_next_eq hom hij, prev_d_eq hom hij, preadditive.comp_add, preadditive.add_comp,
      eq1, eq2, add_zero, zero_add, category.assoc],
  end }

/-- Variant of `null_homotopic_map` where the input consists only of the
relevant maps `C_i ⟶ D_j` such that `c.rel j i`. -/
def null_homotopic_map' (h : Π i j, c.rel j i → (C.X i ⟶ D.X j)) : C ⟶ D :=
null_homotopic_map (λ i j, dite (c.rel j i) (h i j) (λ _, 0))

/-- Compatibility of `null_homotopic_map` with the postcomposition by a morphism
of complexes. -/
lemma null_homotopic_map_comp (hom : Π i j, C.X i ⟶ D.X j) (g : D ⟶ E) :
null_homotopic_map hom ≫ g = null_homotopic_map (λ i j, hom i j ≫ g.f j) :=
begin
  ext n,
  dsimp [null_homotopic_map, from_next, to_prev, add_monoid_hom.mk'_apply],
  simp only [preadditive.add_comp, category.assoc, g.comm],
end

/-- Compatibility of `null_homotopic_map'` with the postcomposition by a morphism
of complexes. -/
lemma null_homotopic_map'_comp (hom : Π i j, c.rel j i → (C.X i ⟶ D.X j)) (g : D ⟶ E) :
null_homotopic_map' hom ≫ g = null_homotopic_map' (λ i j hij, hom i j hij ≫ g.f j) :=
begin
  ext n,
  erw null_homotopic_map_comp,
  congr',
  ext i j,
  split_ifs,
  { refl, },
  { rw zero_comp, },
end

/-- Compatibility of `null_homotopic_map` with the precomposition by a morphism
of complexes. -/
lemma comp_null_homotopic_map (f : C ⟶ D) (hom : Π i j, D.X i ⟶ E.X j) :
f ≫ null_homotopic_map hom = null_homotopic_map (λ i j, f.f i ≫ hom i j) :=
begin
  ext n,
  dsimp [null_homotopic_map, from_next, to_prev, add_monoid_hom.mk'_apply],
  simp only [preadditive.comp_add, category.assoc, f.comm_assoc],
end

/-- Compatibility of `null_homotopic_map'` with the precomposition by a morphism
of complexes. -/
lemma comp_null_homotopic_map' (f : C ⟶ D) (hom : Π i j, c.rel j i → (D.X i ⟶ E.X j)) :
f ≫ null_homotopic_map' hom = null_homotopic_map' (λ i j hij, f.f i ≫ hom i j hij) :=
begin
  ext n,
  erw comp_null_homotopic_map,
  congr',
  ext i j,
  split_ifs,
  { refl, },
  { rw comp_zero, },
end

/-- Compatibility of `null_homotopic_map` with the application of additive functors -/
lemma map_null_homotopic_map {W : Type*} [category W] [preadditive W]
  (G : V ⥤ W) [G.additive] (hom : Π i j, C.X i ⟶ D.X j) :
  (G.map_homological_complex c).map (null_homotopic_map hom) =
  null_homotopic_map (λ i j, G.map (hom i j)) :=
begin
  ext i,
  dsimp [null_homotopic_map, d_next, prev_d],
  simp only [G.map_comp, functor.map_add],
end

/-- Compatibility of `null_homotopic_map'` with the application of additive functors -/
lemma map_null_homotopic_map' {W : Type*} [category W] [preadditive W]
  (G : V ⥤ W) [G.additive] (hom : Π i j, c.rel j i → (C.X i ⟶ D.X j)) :
  (G.map_homological_complex c).map (null_homotopic_map' hom) =
  null_homotopic_map' (λ i j hij, G.map (hom i j hij)) :=
begin
  ext n,
  erw map_null_homotopic_map,
  congr',
  ext i j,
  split_ifs,
  { refl, },
  { rw G.map_zero, }
end

/-- Tautological construction of the `homotopy` to zero for maps constructed by
`null_homotopic_map`, at least when we have the `zero'` condition. -/
@[simps]
def null_homotopy (hom : Π i j, C.X i ⟶ D.X j) (zero' : ∀ i j, ¬ c.rel j i → hom i j = 0) :
  homotopy (null_homotopic_map hom) 0 :=
{ hom := hom,
  zero' := zero',
  comm := by { intro i, rw [homological_complex.zero_f_apply, add_zero], refl, }, }

/-- Homotopy to zero for maps constructed with `null_homotopic_map'` -/
@[simps]
def null_homotopy' (h : Π i j, c.rel j i → (C.X i ⟶ D.X j)) :
  homotopy (null_homotopic_map' h) 0 :=
begin
  apply null_homotopy (λ i j, dite (c.rel j i) (h i j) (λ _, 0)),
  intros i j hij,
  dsimp,
  rw [dite_eq_right_iff],
  intro hij',
  exfalso,
  exact hij hij',
end

/-! This lemma and the following ones can be used in order to compute
the degreewise morphisms induced by the null homotopic maps constructed
with `null_homotopic_map` or `null_homotopic_map'` -/
@[simp]
lemma null_homotopic_map_f {k₂ k₁ k₀ : ι} (r₂₁ : c.rel k₂ k₁) (r₁₀ : c.rel k₁ k₀)
  (hom : Π i j, C.X i ⟶ D.X j) :
  (null_homotopic_map hom).f k₁ = C.d k₁ k₀ ≫ hom k₀ k₁ + hom k₁ k₂ ≫ D.d k₂ k₁ :=
by { dsimp only [null_homotopic_map], rw [d_next_eq hom r₁₀, prev_d_eq hom r₂₁], }

@[simp]
lemma null_homotopic_map'_f {k₂ k₁ k₀  : ι} (r₂₁ : c.rel k₂ k₁) (r₁₀ : c.rel k₁ k₀)
  (h : Π i j, c.rel j i → (C.X i ⟶ D.X j)) :
  (null_homotopic_map' h).f k₁ = C.d k₁ k₀ ≫ h k₀ k₁ r₁₀ + h k₁ k₂ r₂₁ ≫ D.d k₂ k₁ :=
begin
  simp only [← null_homotopic_map'],
  rw null_homotopic_map_f r₂₁ r₁₀ (λ i j, dite (c.rel j i) (h i j) (λ _, 0)),
  dsimp,
  split_ifs,
  refl,
end

@[simp]
lemma null_homotopic_map_f_of_not_rel_left {k₁ k₀ : ι} (r₁₀ : c.rel k₁ k₀)
  (hk₀ : ∀ l : ι, ¬c.rel k₀ l)
  (hom : Π i j, C.X i ⟶ D.X j) :
  (null_homotopic_map hom).f k₀ = hom k₀ k₁ ≫ D.d k₁ k₀ :=
begin
  dsimp only [null_homotopic_map],
  rw [prev_d_eq hom r₁₀, d_next, add_monoid_hom.mk'_apply, C.shape, zero_comp, zero_add],
  exact hk₀ _
end

@[simp]
lemma null_homotopic_map'_f_of_not_rel_left {k₁ k₀ : ι} (r₁₀ : c.rel k₁ k₀)
  (hk₀ : ∀ l : ι, ¬c.rel k₀ l)
  (h : Π i j, c.rel j i → (C.X i ⟶ D.X j)) :
  (null_homotopic_map' h).f k₀ = h k₀ k₁ r₁₀ ≫ D.d k₁ k₀ :=
begin
  simp only [← null_homotopic_map'],
  rw null_homotopic_map_f_of_not_rel_left r₁₀ hk₀ (λ i j, dite (c.rel j i) (h i j) (λ _, 0)),
  dsimp,
  split_ifs,
  refl,
end

@[simp]
lemma null_homotopic_map_f_of_not_rel_right {k₁ k₀ : ι} (r₁₀ : c.rel k₁ k₀)
  (hk₁ : ∀ l : ι, ¬c.rel l k₁)
  (hom : Π i j, C.X i ⟶ D.X j) :
  (null_homotopic_map hom).f k₁ = C.d k₁ k₀ ≫ hom k₀ k₁ :=
begin
  dsimp only [null_homotopic_map],
  rw [d_next_eq hom r₁₀, prev_d, add_monoid_hom.mk'_apply, D.shape, comp_zero, add_zero],
  exact hk₁ _,
end

@[simp]
lemma null_homotopic_map'_f_of_not_rel_right {k₁ k₀ : ι} (r₁₀ : c.rel k₁ k₀)
  (hk₁ : ∀ l : ι, ¬c.rel l k₁)
  (h : Π i j, c.rel j i → (C.X i ⟶ D.X j)) :
  (null_homotopic_map' h).f k₁ = C.d k₁ k₀ ≫ h k₀ k₁ r₁₀ :=
begin
  simp only [← null_homotopic_map'],
  rw null_homotopic_map_f_of_not_rel_right r₁₀ hk₁ (λ i j, dite (c.rel j i) (h i j) (λ _, 0)),
  dsimp,
  split_ifs,
  refl,
end

@[simp]
lemma null_homotopic_map_f_eq_zero {k₀ : ι}
  (hk₀ : ∀ l : ι, ¬c.rel k₀ l) (hk₀' : ∀ l : ι, ¬c.rel l k₀)
  (hom : Π i j, C.X i ⟶ D.X j) :
  (null_homotopic_map hom).f k₀ = 0 :=
begin
  dsimp [null_homotopic_map, d_next, prev_d],
  rw [C.shape, D.shape, zero_comp, comp_zero, add_zero]; apply_assumption,
end

@[simp]
lemma null_homotopic_map'_f_eq_zero {k₀ : ι}
  (hk₀ : ∀ l : ι, ¬c.rel k₀ l) (hk₀' : ∀ l : ι, ¬c.rel l k₀)
  (h : Π i j, c.rel j i → (C.X i ⟶ D.X j)) :
  (null_homotopic_map' h).f k₀ = 0 :=
begin
  simp only [← null_homotopic_map'],
  exact null_homotopic_map_f_eq_zero hk₀ hk₀'
    (λ i j, dite (c.rel j i) (h i j) (λ _, 0)),
end

/-!
`homotopy.mk_inductive` allows us to build a homotopy of chain complexes inductively,
so that as we construct each component, we have available the previous two components,
and the fact that they satisfy the homotopy condition.

To simplify the situation, we only construct homotopies of the form `homotopy e 0`.
`homotopy.equiv_sub_zero` can provide the general case.

Notice however, that this construction does not have particularly good definitional properties:
we have to insert `eq_to_hom` in several places.
Hopefully this is okay in most applications, where we only need to have the existence of some
homotopy.
-/
section mk_inductive

variables {P Q : chain_complex V ℕ}

@[simp] lemma prev_d_chain_complex (f : Π i j, P.X i ⟶ Q.X j) (j : ℕ) :
  prev_d j f = f j (j+1) ≫ Q.d _ _ :=
begin
  dsimp [prev_d],
  have : (complex_shape.down ℕ).prev j = j + 1 := chain_complex.prev ℕ j,
  congr' 2,
end

@[simp] lemma d_next_succ_chain_complex (f : Π i j, P.X i ⟶ Q.X j) (i : ℕ) :
  d_next (i+1) f = P.d _ _ ≫ f i (i+1) :=
begin
  dsimp [d_next],
  have : (complex_shape.down ℕ).next (i + 1) = i := chain_complex.next_nat_succ _,
  congr' 2,
end

@[simp] lemma d_next_zero_chain_complex (f : Π i j, P.X i ⟶ Q.X j) :
  d_next 0 f = 0 :=
begin
  dsimp [d_next],
  rw [P.shape, zero_comp],
  rw chain_complex.next_nat_zero, dsimp, dec_trivial,
end

variables (e : P ⟶ Q)
  (zero : P.X 0 ⟶ Q.X 1)
  (comm_zero : e.f 0 = zero ≫ Q.d 1 0)
  (one : P.X 1 ⟶ Q.X 2)
  (comm_one : e.f 1 = P.d 1 0 ≫ zero + one ≫ Q.d 2 1)
  (succ : ∀ (n : ℕ)
    (p : Σ' (f : P.X n ⟶ Q.X (n+1)) (f' : P.X (n+1) ⟶ Q.X (n+2)),
      e.f (n+1) = P.d (n+1) n ≫ f + f' ≫ Q.d (n+2) (n+1)),
    Σ' f'' : P.X (n+2) ⟶ Q.X (n+3), e.f (n+2) = P.d (n+2) (n+1) ≫ p.2.1 + f'' ≫ Q.d (n+3) (n+2))

include comm_one comm_zero

/--
An auxiliary construction for `mk_inductive`.

Here we build by induction a family of diagrams,
but don't require at the type level that these successive diagrams actually agree.
They do in fact agree, and we then capture that at the type level (i.e. by constructing a homotopy)
in `mk_inductive`.

At this stage, we don't check the homotopy condition in degree 0,
because it "falls off the end", and is easier to treat using `X_next` and `X_prev`,
which we do in `mk_inductive_aux₂`.
-/
@[simp, nolint unused_arguments]
def mk_inductive_aux₁ :
  Π n, Σ' (f : P.X n ⟶ Q.X (n+1)) (f' : P.X (n+1) ⟶ Q.X (n+2)),
    e.f (n+1) = P.d (n+1) n ≫ f + f' ≫ Q.d (n+2) (n+1)
| 0 := ⟨zero, one, comm_one⟩
| 1 := ⟨one, (succ 0 ⟨zero, one, comm_one⟩).1, (succ 0 ⟨zero, one, comm_one⟩).2⟩
| (n+2) :=
  ⟨(mk_inductive_aux₁ (n+1)).2.1,
    (succ (n+1) (mk_inductive_aux₁ (n+1))).1,
    (succ (n+1) (mk_inductive_aux₁ (n+1))).2⟩

section

/--
An auxiliary construction for `mk_inductive`.
-/
@[simp]
def mk_inductive_aux₂ :
  Π n, Σ' (f : P.X_next n ⟶ Q.X n) (f' : P.X n ⟶ Q.X_prev n), e.f n = P.d_from n ≫ f + f' ≫ Q.d_to n
| 0 := ⟨0, zero ≫ (Q.X_prev_iso rfl).inv, by simpa using comm_zero⟩
| (n+1) := let I := mk_inductive_aux₁ e zero comm_zero one comm_one succ n in
  ⟨(P.X_next_iso rfl).hom ≫ I.1, I.2.1 ≫ (Q.X_prev_iso rfl).inv, by simpa using I.2.2⟩

lemma mk_inductive_aux₃ (i j : ℕ) (h : i+1 = j) :
  (mk_inductive_aux₂ e zero comm_zero one comm_one succ i).2.1 ≫ (Q.X_prev_iso h).hom
    = (P.X_next_iso h).inv ≫ (mk_inductive_aux₂ e zero comm_zero one comm_one succ j).1 :=
by subst j; rcases i with (_|_|i); { dsimp, simp, }

/--
A constructor for a `homotopy e 0`, for `e` a chain map between `ℕ`-indexed chain complexes,
working by induction.

You need to provide the components of the homotopy in degrees 0 and 1,
show that these satisfy the homotopy condition,
and then give a construction of each component,
and the fact that it satisfies the homotopy condition,
using as an inductive hypothesis the data and homotopy condition for the previous two components.
-/
def mk_inductive : homotopy e 0 :=
{ hom := λ i j, if h : i + 1 = j then
    (mk_inductive_aux₂ e zero comm_zero one comm_one succ i).2.1 ≫ (Q.X_prev_iso h).hom
  else
    0,
  zero' := λ i j w, by rwa dif_neg,
  comm := λ i, begin
    dsimp, simp only [add_zero],
    convert (mk_inductive_aux₂ e zero comm_zero one comm_one succ i).2.2,
    { cases i,
      { dsimp [from_next], rw dif_neg,
        simp only [chain_complex.next_nat_zero, nat.one_ne_zero, not_false_iff], },
      { dsimp [from_next], rw dif_pos, swap, { simp only [chain_complex.next_nat_succ] },
        have aux : (complex_shape.down ℕ).next i.succ = i := chain_complex.next_nat_succ i,
        rw mk_inductive_aux₃ e zero comm_zero one comm_one succ
          ((complex_shape.down ℕ).next i.succ) (i+1) (by rw aux),
        dsimp [X_next_iso], erw category.id_comp, } },
    { dsimp [to_prev], rw dif_pos, swap, { simp only [chain_complex.prev] },
      dsimp [X_prev_iso], erw category.comp_id, },
  end, }

end

end mk_inductive

/-!
`homotopy.mk_coinductive` allows us to build a homotopy of cochain complexes inductively,
so that as we construct each component, we have available the previous two components,
and the fact that they satisfy the homotopy condition.
-/
section mk_coinductive

variables {P Q : cochain_complex V ℕ}

@[simp] lemma d_next_cochain_complex (f : Π i j, P.X i ⟶ Q.X j) (j : ℕ) :
  d_next j f = P.d _ _ ≫ f (j+1) j :=
begin
  dsimp [d_next],
  have : (complex_shape.up ℕ).next j = j + 1 := cochain_complex.next ℕ j,
  congr' 2,
end

@[simp] lemma prev_d_succ_cochain_complex (f : Π i j, P.X i ⟶ Q.X j) (i : ℕ) :
  prev_d (i+1) f = f (i+1) _ ≫ Q.d i (i+1) :=
begin
  dsimp [prev_d],
  have : (complex_shape.up ℕ).prev (i+1) = i := cochain_complex.prev_nat_succ i,
  congr' 2,
end

@[simp] lemma prev_d_zero_cochain_complex (f : Π i j, P.X i ⟶ Q.X j) :
  prev_d 0 f = 0 :=
begin
  dsimp [prev_d],
  rw [Q.shape, comp_zero],
  rw [cochain_complex.prev_nat_zero], dsimp, dec_trivial,
end

variables (e : P ⟶ Q)
  (zero : P.X 1 ⟶ Q.X 0)
  (comm_zero : e.f 0 = P.d 0 1 ≫ zero)
  (one : P.X 2 ⟶ Q.X 1)
  (comm_one : e.f 1 = zero ≫ Q.d 0 1 + P.d 1 2 ≫ one)
  (succ : ∀ (n : ℕ)
    (p : Σ' (f : P.X (n+1) ⟶ Q.X n) (f' : P.X (n+2) ⟶ Q.X (n+1)),
      e.f (n+1) = f ≫ Q.d n (n+1) + P.d (n+1) (n+2) ≫ f'),
    Σ' f'' : P.X (n+3) ⟶ Q.X (n+2), e.f (n+2) = p.2.1 ≫ Q.d (n+1) (n+2) + P.d (n+2) (n+3) ≫ f'')

include comm_one comm_zero succ

/--
An auxiliary construction for `mk_coinductive`.

Here we build by induction a family of diagrams,
but don't require at the type level that these successive diagrams actually agree.
They do in fact agree, and we then capture that at the type level (i.e. by constructing a homotopy)
in `mk_coinductive`.

At this stage, we don't check the homotopy condition in degree 0,
because it "falls off the end", and is easier to treat using `X_next` and `X_prev`,
which we do in `mk_inductive_aux₂`.
-/
@[simp, nolint unused_arguments]
def mk_coinductive_aux₁ :
  Π n, Σ' (f : P.X (n+1) ⟶ Q.X n) (f' : P.X (n+2) ⟶ Q.X (n+1)),
    e.f (n+1) = f ≫ Q.d n (n+1) + P.d (n+1) (n+2) ≫ f'
| 0 := ⟨zero, one, comm_one⟩
| 1 := ⟨one, (succ 0 ⟨zero, one, comm_one⟩).1, (succ 0 ⟨zero, one, comm_one⟩).2⟩
| (n+2) :=
  ⟨(mk_coinductive_aux₁ (n+1)).2.1,
    (succ (n+1) (mk_coinductive_aux₁ (n+1))).1,
    (succ (n+1) (mk_coinductive_aux₁ (n+1))).2⟩

section

/--
An auxiliary construction for `mk_inductive`.
-/
@[simp]
def mk_coinductive_aux₂ :
  Π n, Σ' (f : P.X n ⟶ Q.X_prev n) (f' : P.X_next n ⟶ Q.X n),
    e.f n = f ≫ Q.d_to n + P.d_from n ≫ f'
| 0 := ⟨0, (P.X_next_iso rfl).hom ≫ zero, by simpa using comm_zero⟩
| (n+1) := let I := mk_coinductive_aux₁ e zero comm_zero one comm_one succ n in
  ⟨I.1 ≫ (Q.X_prev_iso rfl).inv, (P.X_next_iso rfl).hom ≫ I.2.1, by simpa using I.2.2⟩

lemma mk_coinductive_aux₃ (i j : ℕ) (h : i + 1 = j) :
  (P.X_next_iso h).inv ≫ (mk_coinductive_aux₂ e zero comm_zero one comm_one succ i).2.1
    = (mk_coinductive_aux₂ e zero comm_zero one comm_one succ j).1 ≫ (Q.X_prev_iso h).hom :=
by subst j; rcases i with (_|_|i); { dsimp, simp, }

/--
A constructor for a `homotopy e 0`, for `e` a chain map between `ℕ`-indexed cochain complexes,
working by induction.

You need to provide the components of the homotopy in degrees 0 and 1,
show that these satisfy the homotopy condition,
and then give a construction of each component,
and the fact that it satisfies the homotopy condition,
using as an inductive hypothesis the data and homotopy condition for the previous two components.
-/
def mk_coinductive : homotopy e 0 :=
{ hom := λ i j, if h : j + 1 = i then
    (P.X_next_iso h).inv ≫ (mk_coinductive_aux₂ e zero comm_zero one comm_one succ j).2.1
  else
    0,
  zero' := λ i j w, by rwa dif_neg,
  comm := λ i, begin
    dsimp,
    rw [add_zero, add_comm],
    convert (mk_coinductive_aux₂ e zero comm_zero one comm_one succ i).2.2 using 2,
    { cases i,
      { dsimp [to_prev], rw dif_neg,
        simp only [cochain_complex.prev_nat_zero, nat.one_ne_zero, not_false_iff], },
      { dsimp [to_prev], rw dif_pos, swap, { simp only [cochain_complex.prev_nat_succ] },
        have aux : (complex_shape.up ℕ).prev i.succ = i := cochain_complex.prev_nat_succ i,
        rw mk_coinductive_aux₃ e zero comm_zero one comm_one succ
          ((complex_shape.up ℕ).prev i.succ) (i+1) (by rw aux),
        dsimp [X_prev_iso], erw category.comp_id, } },
    { dsimp [from_next], rw dif_pos, swap, { simp only [cochain_complex.next] },
      dsimp [X_next_iso], erw category.id_comp, },
  end }

end

end mk_coinductive

end homotopy

/--
A homotopy equivalence between two chain complexes consists of a chain map each way,
and homotopies from the compositions to the identity chain maps.

Note that this contains data;
arguably it might be more useful for many applications if we truncated it to a Prop.
-/
structure homotopy_equiv (C D : homological_complex V c) :=
(hom : C ⟶ D)
(inv : D ⟶ C)
(homotopy_hom_inv_id : homotopy (hom ≫ inv) (𝟙 C))
(homotopy_inv_hom_id : homotopy (inv ≫ hom) (𝟙 D))

namespace homotopy_equiv

/-- Any complex is homotopy equivalent to itself. -/
@[refl] def refl (C : homological_complex V c) : homotopy_equiv C C :=
{ hom := 𝟙 C,
  inv := 𝟙 C,
  homotopy_hom_inv_id := by simp,
  homotopy_inv_hom_id := by simp, }

instance : inhabited (homotopy_equiv C C) := ⟨refl C⟩

/-- Being homotopy equivalent is a symmetric relation. -/
@[symm] def symm
  {C D : homological_complex V c} (f : homotopy_equiv C D) :
  homotopy_equiv D C :=
{ hom := f.inv,
  inv := f.hom,
  homotopy_hom_inv_id := f.homotopy_inv_hom_id,
  homotopy_inv_hom_id := f.homotopy_hom_inv_id, }

/-- Homotopy equivalence is a transitive relation. -/
@[trans] def trans
  {C D E : homological_complex V c} (f : homotopy_equiv C D) (g : homotopy_equiv D E) :
  homotopy_equiv C E :=
{ hom := f.hom ≫ g.hom,
  inv := g.inv ≫ f.inv,
  homotopy_hom_inv_id := by simpa using
    ((g.homotopy_hom_inv_id.comp_right_id f.inv).comp_left f.hom).trans f.homotopy_hom_inv_id,
  homotopy_inv_hom_id := by simpa using
    ((f.homotopy_inv_hom_id.comp_right_id g.hom).comp_left g.inv).trans g.homotopy_inv_hom_id, }

end homotopy_equiv

variables [has_equalizers V] [has_cokernels V] [has_images V] [has_image_maps V]

/--
Homotopic maps induce the same map on homology.
-/
theorem homology_map_eq_of_homotopy (h : homotopy f g) (i : ι) :
  (homology_functor V c i).map f = (homology_functor V c i).map g :=
begin
  dsimp [homology_functor],
  apply eq_of_sub_eq_zero,
  ext,
  simp only [homology.π_map, comp_zero, preadditive.comp_sub],
  dsimp [kernel_subobject_map],
  simp_rw [h.comm i],
  simp only [zero_add, zero_comp, d_next_eq_d_from_from_next, kernel_subobject_arrow_comp_assoc,
    preadditive.comp_add],
  rw [←preadditive.sub_comp],
  simp only [category_theory.subobject.factor_thru_add_sub_factor_thru_right],
  erw [subobject.factor_thru_of_le (D.boundaries_le_cycles i)],
  { simp, },
  { rw [prev_d_eq_to_prev_d_to, ←category.assoc],
    apply image_subobject_factors_comp_self, },
end

/-- Homotopy equivalent complexes have isomorphic homologies. -/
def homology_obj_iso_of_homotopy_equiv (f : homotopy_equiv C D) (i : ι) :
  (homology_functor V c i).obj C ≅ (homology_functor V c i).obj D :=
{ hom := (homology_functor V c i).map f.hom,
  inv := (homology_functor V c i).map f.inv,
  hom_inv_id' := begin
    rw [←functor.map_comp, homology_map_eq_of_homotopy f.homotopy_hom_inv_id,
      category_theory.functor.map_id],
  end,
  inv_hom_id' := begin
    rw [←functor.map_comp, homology_map_eq_of_homotopy f.homotopy_inv_hom_id,
      category_theory.functor.map_id],
  end, }

end

namespace category_theory

variables {W : Type*} [category W] [preadditive W]

/-- An additive functor takes homotopies to homotopies. -/
@[simps]
def functor.map_homotopy (F : V ⥤ W) [F.additive] {f g : C ⟶ D} (h : homotopy f g) :
  homotopy ((F.map_homological_complex c).map f) ((F.map_homological_complex c).map g) :=
{ hom := λ i j, F.map (h.hom i j),
  zero' := λ i j w, by { rw [h.zero i j w, F.map_zero], },
  comm := λ i, begin
    dsimp [d_next, prev_d] at *,
    rw h.comm i,
    simp only [F.map_add, ← F.map_comp],
    refl
  end, }

/-- An additive functor preserves homotopy equivalences. -/
@[simps]
def functor.map_homotopy_equiv (F : V ⥤ W) [F.additive] (h : homotopy_equiv C D) :
  homotopy_equiv ((F.map_homological_complex c).obj C) ((F.map_homological_complex c).obj D) :=
{ hom := (F.map_homological_complex c).map h.hom,
  inv := (F.map_homological_complex c).map h.inv,
  homotopy_hom_inv_id := begin
    rw [←(F.map_homological_complex c).map_comp, ←(F.map_homological_complex c).map_id],
    exact F.map_homotopy h.homotopy_hom_inv_id,
  end,
  homotopy_inv_hom_id := begin
    rw [←(F.map_homological_complex c).map_comp, ←(F.map_homological_complex c).map_id],
    exact F.map_homotopy h.homotopy_inv_hom_id,
  end }

end category_theory